A School-Based Physical Activity Intervention for Young Children: Are There Effects on Attention and Behavior?. Issue 4 (24th September 2021) - Fedewa, Alicia; Mayo, Molly Rose; Ahn, Soyeon; Erwin, Heather
Abstract: There is a growing body of evidence to support the benefits of physical activity on children's cognitions and behavior. Although children with ADHD are known to be at risk for deficits in cognitive processing, specifically executive functioning which controls the organization, regulation, and planning of behavior, little evidence exists about the effect of vigorous physical activity on executive functioning and the accompanying behavioral and inattention symptoms of ADHD. Given the overwhelming research supporting the need for early intervention in this population and the dearth of research examining the effects of physical activity in children, the present study investigated the effects of a 16 week physical activity intervention in an elementary sample of typical-developing children as well as those at-risk for ADHD. The findings indicated no significant relationship between the physical activity intervention and beneficial outcomes for student executive functioning or ADHD symptomology, although a moderator effect was found for low and high intensity on student executive functioning suggesting that low and high intensity physical activity may improve student executive functioning. Implications for school personnel are provided given the study findings.